Simulating Movement Devices Used in Hospital Evacuation - Hunt, Aoife L. E.; Galea, Edwin R.; Lawrence, Peter J.; Frost, Ian R.; Gwynne, Steven M. V. (Fire technology, 2020)
In hospitals, the evacuation of those with severe movement impairments can be highly problematic for the patients, for the staff and for other evacuees. It is critical to understand the performance of horizontal and vertical evacuation procedures, including the means by which people with reduced mobility can be assisted during stair descent. Microsimulation modelling provides a useful tool to assess evacuation strategies, given the challenges of preparing and transporting patients in need of on-going care and the unfeasibility of real evacuation drills. However, current simulation models typically focus on the movement of individual agents, not the staff-patient interactions and sizable equipment required to carry out assisted evacuation. To address this, the buildingEXODUS evacuation model has been enhanced to represent moving objects in addition to moving individual agents. This paper describes the modelling theory behind this development, where dedicated data has been applied to enable the explicit specification of evacuation devices, operated by agents (for instance, representing the vertical travel speeds achieved—with averages ranging between 0.6 m/s and 0.84 m/s—when employing different movement devices). Algorithms are presented that calculate the movement of devices along corridors, through doorways and in stairway descent, including a method of geometric decomposition of the available hospital evacuation routes. This new functionality addresses the key evacuation components of repeated patient collection and has numerous applications, both in simulating hospital evacuation and in representing evacuation of other premises that include people with reduced mobility. Examination of the performance of this functionality found it predicated performance within 6% of expectation. Once further testing is completed, the resultant tool can be used to significantly enhance planning and diagnostic capabilities related to the evacuation of hospital and other healthcare facilities.